2008
DOI: 10.1051/0004-6361:200809436
|View full text |Cite
|
Sign up to set email alerts
|

Odin observations of the Galactic centre in the 118-GHz band

Abstract: Aims. The Odin satellite has been used to search for the 118.75-GHz line of molecular oxygen (O 2 ) in the Galactic centre. Methods. Odin observations were performed towards the Sgr A * circumnuclear disk (CND), and the Sgr A +20 km s −1 and +50 km s

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 30 publications
2
26
1
Order By: Relevance
“…3), H 2 (Lee et al 2003(Lee et al , 2008, CH 3 OH (Stankovic et al 2007), HC 3 N (Sandqvist et al 2008), SiO (Amo-Baladrón et al 2009, etc., and also through dust submm continuum emission (e.g., Mezger et al 1989;Zylka et al 1990;Dent et al 1993;Lis & Carlstrom 1994). The early CO emission map of Solomon et al (1972) already revealed two massive molecular clouds peaking ≈3 east and ≈2.…”
Section: The Belt Of Molecular Cloudsmentioning
confidence: 99%
“…3), H 2 (Lee et al 2003(Lee et al , 2008, CH 3 OH (Stankovic et al 2007), HC 3 N (Sandqvist et al 2008), SiO (Amo-Baladrón et al 2009, etc., and also through dust submm continuum emission (e.g., Mezger et al 1989;Zylka et al 1990;Dent et al 1993;Lis & Carlstrom 1994). The early CO emission map of Solomon et al (1972) already revealed two massive molecular clouds peaking ≈3 east and ≈2.…”
Section: The Belt Of Molecular Cloudsmentioning
confidence: 99%
“…Chemistry in post-shocked gas driven by neutral-neutral reactions has been invoked to reproduce HNCO abundances on the order of 10 −8 , as the high temperatures achieved by shocks could overcome the energy barriers of these reactions (for more details see Turner et al 1999;Tideswell et al 2010;Rodriguez-Fernandez et al 2010). However, this formation pathway presents two main drawbacks: the short times that shocks can maintain the required high temperatures and cannot detect O 2 in the Sgr A complex (X O 2 ≤ 1.2 × 10 −7 ; Sandqvist et al 2008), a key molecule in this formation path of HNCO.…”
Section: Hnco Chemistrymentioning
confidence: 99%
“…Quan et al (2008, and references therein) present a recent overview for our understanding of the abundance of interstellar molecular oxygen. In general, the amount of O 2 in molecular clouds has been below detection capability of the dedicated space missions SWAS (e.g., Goldsmith et al 2000;Bergin et al 2000) and Odin (e.g., Pagani et al 2003;Sandqvist et al 2008). In merely one single location, viz.…”
Section: Introductionmentioning
confidence: 99%